Use of Geo-Information System in Creating Topological Maps - Hamroqul Ravshanov Amirqulovich; Komil Khujakeldiyev Nosirovich; Jahongir Nosirov Komil o‘g‘li (Web of Journals Publishing, 2023)
The article provides information on the use of GIS in the creation of land use maps using modern technologies for increasing, restoring, assessing and managing the productivity of irriGISed agricultural lands, including space imagery, geoinformation technologies and automated databases.
Keywords: Cadastre, land plots, geographic information systems, geoinformation cartography, thematic maps, cadastral maps, inter-farm land management projects, intra-farm land management projects, modern computer technologies.